2002
DOI: 10.1038/sj.bjc.6600506
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alfa is more potent in vivo and can be administered less frequently than rHuEPO

Abstract: To date, human studies in a dialysis population have confirmed the pharmacokinetic differences in half life and clearance between NESP and r- HuEPO (Macdougall, 1999). However, studies in humans using NESP have shown an efficacy profile that is comparable to r-HuEPO (Coyne et al, 2000; Nissenson et al, 2000; Locatelli et al, 2001). These studies reinforce the fact that results garnered from animal models are not necessarily indicative of what is to be ascertained in humans. REFERENCES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Early attempts to improve rhEPO included enhancing molecular stability or increasing affinity for EPOR [73]. However, increased affinity did not necessarily increase in vivo biological potency, because serum t 1/2 was the primary driver of the degree of response [9,28,74]. The exception was modifications that yielded molecules with an affinity that was too low, resulting in ineffective EPOR dimerization and activation.…”
Section: Potential Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Early attempts to improve rhEPO included enhancing molecular stability or increasing affinity for EPOR [73]. However, increased affinity did not necessarily increase in vivo biological potency, because serum t 1/2 was the primary driver of the degree of response [9,28,74]. The exception was modifications that yielded molecules with an affinity that was too low, resulting in ineffective EPOR dimerization and activation.…”
Section: Potential Strategiesmentioning
confidence: 99%
“…Both endogenous and recombinant EPO have microheterogeneity in carbohydrate structures with variation in sialic acid contentdup to 14 attached sialic acid residues [74,[80][81][82]. The importance of sialic acid content for clearance was noted in experiments with rhEPO isoforms, revealing a direct and positive relationship between sialic acid content and in vivo potency [74].…”
Section: Hyperglycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lasne and colleagues combined diafiltration with IEF and double immunoblotting ( Lasne et al ., 2002 ; Lasne, 2003 ) and demonstrated that rHuEpo had a different ‘fingerprint’ with more basic isoforms compared with urinary eEpo ( Lasne and De Ceaurriz, 2000 ). Some differential clearance of the most basic isoforms of rHuEpo ( Egrie and Browne, 2002a ) resulted in an enrichment of the more acidic species over time ( Catlin et al ., 2002 ; Lasne et al ., 2002 , 2007a ; Breidbach et al ., 2003 ); however, the pattern of administered rHuEpo compared with rHuEpo excreted in urine was not substantially altered. Thus, when used appropriately, the test can detect doping with rHuEpo.…”
Section: Agents Used In Dopingmentioning
confidence: 99%
“…These products differ in their biochemical structure, pharmacokinetic profile, and receptor-binding affinity. 65,66 The amino acid sequence of epoetin alfa, produced with recombinant DNA technology, is identical to that of endogenous erythropoietin. In contrast, darbepoetin alfa differs from the endogenous human protein in several respects, including five amino acid mutations and a higher molecular weight, which is due, in part, to increased carbohydrate content (~52% carbohydrate for darbepoetin alfa vs ~40% carbohydrate for epoetin alfa).…”
Section: Erythropoiesis-stimulating Agentsmentioning
confidence: 99%